2021
DOI: 10.1016/j.kint.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COVID-19 versus influenza on the incidence, features, and recovery from acute kidney injury in hospitalized United States Veterans

Abstract: Acute kidney injury is a common complication in patients hospitalized with SARSCoV-2 (COVID-19), with prior studies implicating multiple potential mechanisms of injury. Although COVID-19 is often compared to other respiratory viral illnesses, few formal comparisons of these viruses on kidney health exist. In this retrospective cohort study, we compared the incidence, features, and outcomes of acute kidney injury among Veterans hospitalized with COVID-19 or influenza and adjusted for baseline conditions using w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 41 publications
(43 reference statements)
1
35
0
3
Order By: Relevance
“…2 b) [ 31 ]. Additionally, rates of AKI and need for dialysis were much greater during the course of COVID-19 compared to influenza respiratory infections, as demonstrated by large scale comparison studies [ 32 , 33 ]. Many mechanisms of kidney involvement in the acute phase of COVID-19 have been proposed: systemic factors including hemodynamic instability in response to sepsis or multi-organ failure (most commonly found in the so-called pre-renal AKI), cytokine-mediated injury and direct viral invasion, as described in the previous section.…”
Section: Kidney Involvement In the Acute Phase Of Covid-19mentioning
confidence: 99%
“…2 b) [ 31 ]. Additionally, rates of AKI and need for dialysis were much greater during the course of COVID-19 compared to influenza respiratory infections, as demonstrated by large scale comparison studies [ 32 , 33 ]. Many mechanisms of kidney involvement in the acute phase of COVID-19 have been proposed: systemic factors including hemodynamic instability in response to sepsis or multi-organ failure (most commonly found in the so-called pre-renal AKI), cytokine-mediated injury and direct viral invasion, as described in the previous section.…”
Section: Kidney Involvement In the Acute Phase Of Covid-19mentioning
confidence: 99%
“…The incidence and the severity of AKI are affected by multiple comorbidity factors such as CKD, hypertension, diabetes, congestive heart failure, and age [ 23 ]. AKI occurred in nearly half of all patients hospitalized with COVID-19 and the majority of those admitted to the intensive care unit [ 22 , 24 ]. AKI is also associated with high mortality [ 25 ].…”
Section: Epidemiology and Clinical Presentationsmentioning
confidence: 99%
“…Interestingly, an exception to this finding was constituted by patients affected by malignancies who, probably due to the severity of the underlying disease, continued to access the hospital also during the pandemic, as proved by the increased prevalence of these patients among SARS-CoV-2-negative patients admitted in the COVID-19 period. Finally, it is not possible to rule out that the different outcomes during the pandemic were also correlated with peculiar pathogenic mechanisms of AKI developing in SARS-CoV-2-infected patients [ 18 ]. Moreover, looking again at the kidney function, we found that sCr levels at discharge were significantly higher in patients hospitalized in the COVID-19 period compared to the pre-COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%